PENGEMBANGAN UMKM DI KELURAHAN SEI JANG BERBASIS LITERASI DIGITAL PADA UMKM ANS 3 BERSAUDARA - Abriyoso, Octo Jaya (P3M STIE Pembangunan Tanjungpinang, 2024)
This service aims to develop digital literacy-based MSMEs for business actors in the Sei Jang Village, Tanjungpinang City. One of the SMEs in the Seijang village, Bukit Bestari sub-district, is the 3 Brothers ANS UMKM. The methods in this service are surveys, training, and direct assistance in the field with the aim of MSME owners having new knowledge about digitizing MSMEs that every msme should have done and used this digital literacy, which can be obtained at low cost and free of charge